2011
DOI: 10.1210/en.2010-1100
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Deficiency and Diet-Induced Obesity Reduce Hypothalamic Kisspeptin Expression in Mice

Abstract: The hormone leptin modulates a diverse range of biological functions, including energy homeostasis and reproduction. Leptin promotes GnRH function via an indirect action on forebrain neurons. We tested whether leptin deficiency or leptin resistance due to a high-fat diet (HFD) can regulate the potent reproductive neuropeptide kisspeptin. In mice with normalized levels of estradiol, leptin deficiency markedly reduced kisspeptin gene expression, particularly in the arcuate nucleus (ARC), and kisspeptin immunorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
163
3
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(187 citation statements)
references
References 45 publications
15
163
3
3
Order By: Relevance
“…Here, female DBA/2J mice made obese by maintenance on a high-fat diet from weaning to adulthood had reduced Kiss1 mRNA in the ARC and the AVPV compared with chow-fed controls. Consistent with this, kisspeptin neuron number (as detected by immunohistochemistry) was also reduced in the latter (Quennell et al 2011).…”
Section: Metabolic Control Of Fertilitysupporting
confidence: 79%
See 1 more Smart Citation
“…Here, female DBA/2J mice made obese by maintenance on a high-fat diet from weaning to adulthood had reduced Kiss1 mRNA in the ARC and the AVPV compared with chow-fed controls. Consistent with this, kisspeptin neuron number (as detected by immunohistochemistry) was also reduced in the latter (Quennell et al 2011).…”
Section: Metabolic Control Of Fertilitysupporting
confidence: 79%
“…It is likely that this result reflects redundancy in kisspeptin neurons and signaling as genetically targeted mice with 50 and 95% reductions in Kiss1 transcript still maintain, albeit impaired in females, fertility (Popa et al 2013). In addition, the DBA/2J mouse strain possess less than one-tenth the level of Kiss1 mRNA in the brain than the C57BL/6 mice (Quennell et al 2011), yet are fertile. Thus, these data may highlight the importance of kisspeptin in reproduction, in that it is synthesized in excess to ensure reproductive success.…”
Section: Kisspeptin Governs Puberty Onset and Reproductionmentioning
confidence: 99%
“…Of note, the neuroanatomy of such a pathway is yet to be elucidated. In fact, recent studies revealed that the downstream target of mTOR, pS6, is not apparently expressed in Kiss1 neurons (67), hence reinforcing the view of a predominant indirect mode of action of leptin/mTOR signals on kisspeptin pathways.…”
Section: Kisspeptins: Major Gatekeepers Of Pubertymentioning
confidence: 86%
“…Although kisspeptin gene (Kiss1) expression is primarily regulated by gonadal steroid hormones (Smith 2009), it is also modulated by metabolic status such that its expression becomes reduced in response to metabolic stress, such as fasting (Castellano et al 2005) or prolonged high-fat diet feeding (Quennell et al 2011). Approximately 40% of ARC kisspeptin neurons were shown to express the gene for LepR (Smith et al 2006) in one report, but subsequent work suggests a more modest level of co-expression (Louis et al 2011, Cravo et al 2013) and failed to show direct leptin-kisspeptin signaling (Quennell et al 2011). InsR protein expression was also observed in a subset of kisspeptin immunoreactive neurons (Evans et al 2014a).…”
Section: Kisspeptin-expressing Neuronsmentioning
confidence: 99%